Electric Circuits and Networks : For GTU. - Kumar, Suresh (2010)
Electric Circuits and Networks: For GTU is designed to serve as a textbook for an undergraduate course on basic electric circuits and networks. Spread over eleven chapters, it can be taught with varying degrees of emphasis depending on the course requirements.
8.3.7 Zero-Input Response by Convolution Integral.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books